2009
DOI: 10.1136/adc.2007.132522
|View full text |Cite
|
Sign up to set email alerts
|

Do retinal haemorrhages occur in infants with convulsions?

Abstract: Convulsions alone are unlikely to cause retinal haemorrhages in children under 2 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Resuscitation-related retinal hemorrhages are few in number and confined to the posterior pole [26]. Retinal hemorrhages following seizures are extremely rare, with an incidence across four studies of less than 0.1%, in which only one case had unilateral flame-shaped superficial retinal hemorrhages located just at the optic disc and nowhere else [29][30][31][32]. While valsalva retinopathy characterized by preretinal or vitreous hemorrhage (not intraretinal retinal hemorrhage) is a well-described entity in adults, excessive coughing has not been found to cause retinal hemorrhage in young children [33].…”
Section: Differential Diagnosismentioning
confidence: 97%
“…Resuscitation-related retinal hemorrhages are few in number and confined to the posterior pole [26]. Retinal hemorrhages following seizures are extremely rare, with an incidence across four studies of less than 0.1%, in which only one case had unilateral flame-shaped superficial retinal hemorrhages located just at the optic disc and nowhere else [29][30][31][32]. While valsalva retinopathy characterized by preretinal or vitreous hemorrhage (not intraretinal retinal hemorrhage) is a well-described entity in adults, excessive coughing has not been found to cause retinal hemorrhage in young children [33].…”
Section: Differential Diagnosismentioning
confidence: 97%
“…10 Multiple conditions associated with increased intrathoracic pressure, such as seizures, cough, respiratory distress, or vomiting, are not associated with RH in children. [70][71][72][73][74][75][76] Other than a few hemorrhages in the posterior pole, RHs seem to be exceedingly rare after cardiopulmonary resuscitation with chest compressions, [77][78][79][80] including in a pig model. 81 Rare case reports that have suggested otherwise were complicated by multiple confounding systemic factors or poor evaluations to rule out abuse.…”
Section: Increased Intrathoracic Pressurementioning
confidence: 99%
“…[6][7][8] In the literature, RHs have been suggested to occur in association with cardiopulmonary resuscitation (CPR), intracranial hemorrhages, raised intracranial pressure, bleeding diathesis (congenital or acquired), and seizures, 6,7 although the studies determining such an association have not revealed evidence to support all of these implicated etiologies with RH. [9][10][11][12][13][14][15][16][17][18] Furthermore, RHs in abuse have been observed commonly to be flame-shamed, bilateral, and multilayered, unlike RH seen in other postulated etiologies. 6 Because the majority of studies describing RH focus on patients with AHT, there is potential selection bias with a risk of circular reasoning.…”
mentioning
confidence: 99%